Pola Bakteri Kontaminan Serta Resistensinya di ICU dan Ruang Operasi Pada Rumah Sakit di Bandar Lampung - Tuntun, Maria (Department of Health Analyst, Politeknik Kesehatan, Kementerian Kesehatan Tanjungkarang, 2022)
The ICU and operating rooms are places where sterility must be maintained. The purpose of this study was to determine the pattern of bacterial contaminants and their resistance in the ICU and operating rooms of several hospitals in Bandar Lampung. This type of research is descriptive, with a cross sectional design. Held in September – November 2019, at three hospitals which are BPJS referral hospitals in Bandar Lampung City, Indonesia. Samples were taken in the ICU and operating rooms by swab on walls, floors, beds, officers' clothes, equipment, and air samples. Sample examination includes microscopic examination, isolation, identification andantibiotic sensitivity testing. The results showed that from 54 samples examined, 61 isolates of contaminant bacteria were grouped into 11 bacterial species. The patterns of gram negative contaminants were Proteus morganii (19.7%), Pseudomonas aeroginosa (11.5%), and Proteus mirabilis (9.8%). The Gram positive bacteriawere dominated by Staphylococcus aureus (13.1%). Proteus mirabilis bacteria were resistant (16.7% - 100%) to 9 antibiotics used in this study. Klebsiella pneumonia, E. coli and Staphylococcus aureus, on average were 56.82%, 54.55% and 45.45% resistant to antibiotics. Some bacterial species are still sensitive to ciprofloxacinand meropenem. The conclusion is that pathogenic bacteria are still found on the surfaces of objects in the ICU and operating rooms, and these bacteria are resistant to antibiotics.